Benzothiazoles: How relevant in cancer drug design strategy? - Singh M.; Singh S.K. (My University, 2025)
Heterocyclic compounds, analogs and derivatives have attracted attention due to their diverse biological and pharmacological properties. Benzoheterocycles such as benzothiazoles, benzimidazoles and benzoxazoles are constituents of many bioactive heterocyclic compounds, having wider range of applications. They have been extensively studied for their biological activities, and can serve as unique and versatile scaffolds for drug design. The benzothiazole, in the family of heterocyclic compounds has assumed special significance in synthetic chemistry, pharmaceutical chemistry as well as in clinical applications because of its anti-tumor properties. This review is organized in the following ways. It begins with brief introduction on the chemical diversity of synthetic analogs of benzothiazole. After this, drug design strategy and mechanisms of action through its diverse biological targets in which benzothiazole and its derivatives display their anticancer activity are discussed. It ends with the metabolism pattern of benzothiazole and its analogs. Analysis of the structure-activity relationships (SAR), quantitative structure-activity relationships (QSAR) as well as on docking studies of this family of compounds highlights the potential that may lead to the development of novel anticancer agents. Such relationships will definitely create lot of interest among the researchers to synthesize optimized variety of benzothiazole derivatives and to screen them for their anticancer activity. © 2014 Bentham Science Publishers.